Polymer carriers for anticancer drugs targeted to EGF receptor - Studenovsky, Martin; Pola, Robert; Pechar, Michal; Etrych, Tomas; Ulbrich, Karel; Kovar, Lubomir; Kabesova, Martina; Rihova, Blanka (Macromolecular bioscience, 2012)
A novel actively targeted polymer carrier for anticancer drugs based on an N-(2-hydroxypropyl)methacrylamide copolymer (PHPMA) is proposed. An oligopeptide sequence GE7, attached to the polymer, is a specific ligand for the EGF receptor overexpressed on most tumor cells. Co-attachment of selected chemotherapeutics will therefore lead to formation of tumor-specific polymer therapeutics, further enhanced by the EPR effect. FACS measurements prove elevated binding activity of the fluorescently labeled PHPMA/GE7 conjugate in EGFR-rich cells (FaDu, MCF-7), compared to conjugates of scrambled peptides. Cell lines with low EGFR level (SW620, B16F10) bind the GE7 conjugate significantly less.
Keywords: Positron-Emission Tomography; lidé; průtoková cytometrie; oligopeptidy; Polymethacrylic Acids; Cell Line, Tumor; Antineoplastic Agents; Flow Cytometry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; spektrofotometrie ultrafialová; kyseliny polymethakrylové; protinádorové látky; Chromatography, High Pressure Liquid; lékové transportní systémy; Drug Delivery Systems; Humans; pozitronová emisní tomografie; vysokoúčinná kapalinová chromatografie; spektrometrie hmotnostní - ionizace laserem za účasti matrice; ErbB Receptors; Oligopeptides; nádorové buněčné linie; Spectrophotometry, Ultraviolet; erbB receptory